Optimizing the Mixture Design of Manufactured Sand Concrete for Highway Guardrails in Mountainous Terrain - Jianping Gao; Pan Zhou; Sigui Zhao; Qian Yang; Kang Gu; Qingnan Song; Zhengwu Jiang (Buildings)
Concrete quality is essential for highway guardrails in mountainous terrain to overcome freeze–thaw cycles, and manufactured sand (MS) concrete is potentially a more sustainable construction material. This paper aims to optimize the mechanical strength and freeze-thaw resistance of MS concrete for highway guardrails. The effects of water-to-binder (W/B) ratio (0.38–0.42), air-entraining agent (AEA) (0–0.5‱), fly ash (FA) (10–30%) and binder contents (360–380 kg/m3) on the properties of MS concrete were investigated. The mechanism behind the factors was further studied with scanning electron microscopy (SEM) and mercury injection porosimetry (MIP). Results showed that increasing W/B ratio, AEA and FA contents led to the reduction of compressive strength, but improved freeze–thaw resistance by reducing the mass loss during the cyclic freeze–thaw. SEM and MIP illustrated that the increase in W/B ratio and AEA addition increased the pore volume and caused a more porous structure, but increasing FA and binder contents densified the structure of MS concrete. This is consistent with the evolution of compressive strength and freeze–thaw resistance. This study offers an optimization method to obtain MS concrete with good compressive strength and freeze–thaw resistance for highway construction.